Adoptive transfer of membrane-restricted IL-12-TCR T cells promotes antigen spreading and elimination of antigen-negative tumor variants - James L Gulley; Ling Zhang; Christian S Hinrichs; John S Davies; Andrew Sinkoe; Wiem Lassoued; Farrah Karimipour; Philip Homan; Daniel Burnett; Scott M Norberg; Alex Kuznetsov; Margaret Cam; et al. (Journal for ImmunoTherapy of Cancer)
Background Adoptive T-cell therapy has demonstrated clinical activity in B-cell malignancies, offering hope for its application to a broad spectrum of cancers. However, a significant portion of patients with solid tumors experience primary or secondary resistance to this treatment modality. Target antigen loss resulting either from non-uniform antigen expression or defects in antigen processing and presentation machinery is one well-characterized resistance mechanism. Constitutively expressed membrane-anchored interleukin-12 (caIL-12) has demonstrated enhanced antitumor activity and low systemic exposure in multiple preclinical adoptive T-cell treatment models with homogeneous tumor antigen expression. In this study, we assess the therapeutic impact of caIL-12 on target antigen-negative variants in syngeneic mouse models.Methods Target antigen-positive tumors were generated by transducing B16F10 melanoma cells (B16) or Lewis Lung Carcinoma cells (LLC) with a construct expressing the OVA antigen, SIINFEKL, tagged to ubiquitin (B16-U-OVA, LLC-U-OVA), while B16 or LLC tumors served as antigen-negative variants. C57BL/6J mice were subcutaneously injected with heterogeneous tumors composed of 80% B16-U-OVA and 20% B16. Bilateral tumors were established by injecting the left flank with B16-U-OVA or LLC-U-OVA tumors and the right flank injected with B16 or LLC tumors. The tumor-bearing mice then underwent 5.5 Gy total body irradiation, followed by adoptive transfer of OT-I TCR-T cells engineered with or without caIL-12.Results TCR-T cells (OT-I) delivered caIL-12 to the B16-U-OVA tumor sites and induced robust tumor control and survival benefits in mice bearing a heterogeneous tumor with OVA-negative variants. caIL-12 exerted its effect on OVA-negative B16 variants primarily by priming and activating endogenous antitumor CD8 T cells via antigen spreading. In addition, antigen spreading induced by OT-I-caIL-12 resulted in controlling OVA-negative tumors implanted at distant sites. This therapeutic effect required antigen-specific TCR-T cells and caIL-12 to colocalize at the tumor site, along with endogenous CD8 T cells capable of recognizing shared tumor antigens.Conclusion Expression of caIL-12 by tumor-targeting T cells demonstrated therapeutic effect against target-antigen-negative tumor variants, primarily through the induction of antigen spreading. These findings highlight the potential of caIL-12 to address challenges of antigen escape and tumor heterogeneity that may limit the efficacy of T-cell therapy against solid tumors.